Testicular biometrics of lambs at different ages fed with different levels of neutral detergent fiber from forage - Macedo Junior, Gilberto de Lima; Assis, Roberta Moura; Perez, Juan Ramón Olalquiaga; Paula, Oiti josé; França, Patricia Maria [UNESP]; Almeida, Thaís Romano Vasconcelos (FapUNIFESP (SciELO), 2014)
The experiment was conducted at the Federal University of Lavras. We used 64 lambs, which, after birth, were divided into four treatments: Diet A - 8.67; Diet B - 17.34, Diet C - 26.01 and Diet D - 34.68% neutral detergent fiber from forage (NDFf) in the diet. At three days of age, lambs were separated from their mothers and began receiving sheep milk replacer until weaning at 55 days. The experimental diets were isonitrogenous, formulated to meet the nutritional requirements of growing lambs, except for energy. Four digestibility diet essays were conducted for determining of metabolizable energy (ME) at different ages (43, 83, 123 and 173 days of life). The biometric variables analyzed were weight, testis weight, scrotal circumference and volume. The experimental design was in randomized blocks (DBC), in a 4 × 4 factorial arrangement (four levels of dietary NDFf and four slaughter ages), with 4 replicates per treatment. The estimation of scrotal circumference by weight proved to be more efficient than in function of age. The prediction of the size and weight of the testes through scrotal circumference was more efficient than by the age and body weight. Animals fed diets with less fiber from forage, that is, with greater amount of energy, showed better results of testis biometry compared to the animals fed smaller amounts of energy.
Biometria testicular de cordeiros em diferentes idades e alimentados com níveis crescentes de fibra em detergente neutro oriunda da forragem
Keywords: Energy; Intake; Puberty; Sheep; Testicle